The Superior Function of the Subplate in Early Neocortical Development - Luhmann, Heiko J.; Kirischuk, Sergei; Kilb, Werner (Frontiers in Neuroanatomy, 2018)
During early development the structure and function of the cerebral cortex is critically organized by subplate neurons (SPNs), a mostly transient population of glutamatergic and GABAergic neurons located below the cortical plate. At the molecular and morphological level SPNs represent a rather diverse population of cells expressing a variety of genetic markers and revealing different axonal-dendritic morphologies. Electrophysiologically SPNs are characterized by their rather mature intrinsic membrane properties and firing patterns. They are connected via electrical and chemical synapses to local and remote neurons, e.g., thalamic relay neurons forming the first thalamocortical input to the cerebral cortex. Therefore SPNs are robustly activated at pre- and perinatal stages by the sensory periphery. Although SPNs play pivotal roles in early neocortical activity, development and plasticity, they mostly disappear by programmed cell death during further maturation. On the one hand, SPNs may be selectively vulnerable to hypoxia-ischemia contributing to brain damage, on the other hand there is some evidence that enhanced survival rates or alterations in SPN distribution may contribute to the etiology of neurological or psychiatric disorders. This review aims to give a comprehensive and up-to-date overview on the many functions of SPNs during early physiological and pathophysiological development of the cerebral cortex.